Peran Komunitas Kakak Asuh sebagai Wujud New Social Movement dalam Bidang Pendidikan - Salsabila, Sofia Salsabila; Hufad, Achmad; Wahyuni, Sri (University of Jember, 2024)
The Kakak Asuh Community has a role in the field of education as a form of new social movement in the field of education. This research aims to describe the role of the Kakak Asuh community community and the forms of movement carried out by the Kakak Asuh community. This research uses a qualitative approach with phenomenological methods. Data collection techniques through observation, interview, and documentation. The validity of data using triangulation of sources, methods, and theories. Data analysis using interactive model The results of the research show that the Kakak Asuh community has a role in the field of education including a facility role, an educational role, a representative role and a technical role which is realized through new forms of social movement action in the form of routine teaching